Tuberculin skin test conversion and association with occupation and demographic characteristics in workers at San Ignacio University Hospital - Ruiz-Morales, Álvaro; Hidalgo-Martínez, Patricia; Pulido-Arenas, Jorge; Mora-Garzón, Edwin; Rojas-Puentes, Juan C (Revista de salud pública (Bogotá, Colombia), 2015)
Objectives To establish the prevalence of positivity and conversion rate of the tuberculin skin test in workers of our hospital, and to describe the related demographic and occupational characteristics. Materials and Methods An observational, descriptive study was conducted in a cohort of hospital workers who underwent the tuberculin skin test. The positivity of the test was defined as a result of greater than or equal to 10 mm, and conversion was defined as an increase of 6 or 10 mm with respect to the initial test. Results Prevalence of 23.7 % and incidence of conversion of 13.6 % for the major cut-off point of 10 mm, and 23 % for the lesser cut-off point of 6 mm, was found. The age of the subjects was related to the conversion, but there was no relation with occupation. Conclusions The probability of tuberculosis transmission in health-care workers is higher than in the general population. Promotion and prevention measures must be implemented to decrease the transmission and to increase awareness of tuberculosis related to occupational activities.